The Development of Learning Media of RiTAS Application Oriented to Ausubel Learning Theory for Social Studies Content of Grade VI - Ferdiansyah, Ade Citia Dewi; Wulandari, I Gusti Agung Ayu (Journal of Education Technology, 2021)
Teachers and students encounter obstacles while online learning during the pandemic. Online learning because students bored if only using learning media in the form of videos taken from YouTube and assignments given by teachers through Google Classroom and Whatsapp groups. The limited ability of teachers to use digital learning media is the cause of the monotony of learning media during online learning. The purpose of this study was to describe the design and validity of the developed application learning media. This development research applied the ADDIE model. The data collected used a questionnaire method with a questionnaire instrument. Data analysis used qualitative and quantitative descriptive analysis method. The subject of this development research is a learning media in the form of an android application. Afterward the subject content reviewed by expert validators, learning design experts, media experts.Â  Finally conducted trials by students in individual and small group. The results of data analysis based on media validation by content experts obtained a score of 92.8% with very good qualifications, learning design experts obtained a score of 87.5% with good qualifications, learning media experts obtained a score of 85% with good qualifications. The results of individual trials on 3 students obtained a score of 90.1% with very good qualifications and a test through a small group test on 9 students obtained a score of 90.9% with very good qualifications. Based on the results of data analysis product test by experts and the testing results on students, it is concluded that the learning media of this study are valid to be used in learning by students grade VI.